FORMS AND FACTORS CAUSING MORAL DECADENCE OF THE MILLENNIAL GENERATION IN SOCIAL COMMUNITY - Saddam Hakki (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
This research is motivated by the moral decadence in the current millennial era when the flow of modernization is able to present everything that has an impact on the moral decline of the Indonesian population, especially among the youth. The moral crisis experienced, especially among youth, has become widespread and could threaten the future of the nation. The aim of this research is to describe the forms and factors causing the moral decadence of the millennial generation in society's social life. This research was carried out using library research , which is research whose objects are searched for using various library information such as books, scientific journals, magazines, newspapers and documents . If researchers do not have their own reading sources, they can look in libraries, both formal institutional libraries and private libraries. The results of the research show that cultivating character in the family environment is not enough for moral construction because when they grow up the child will find a new environment which will also shape his personality. Cultivating character in the family environment will become the foundation for further character, but quite a few experience setbacks due to the influence of the new environment. In constructing the moral generation of the nation, three elements of the state which include society, government and the private sector must build synergy in creating Indonesia's golden generation. Meanwhile, the government, with its main duties as a policy maker, can create educational regulations that are oriented towards instilling noble values, as well as developing the character of young Indonesian intellectuals. Character development in formal education institutions has not achieved the expected output. Much of character education is in the form of theory, without any room for implementation of character or moral values. Furthermore, the presence of human rights (HAM) also becomes a pathology in character development, because human rights indirectly limit the domination of teaching staff over students.